Analisis Deskriptif Budaya Organisasi di Lingkungan Dosen Tetap PTS Swasta Wilayah Sumatera Selatan - Muhammad Helmi (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2021)
The background of this research departs from the phenomenon of the demands of the times, which require the world of higher education to produce superior and competitive human resources in the economic field. This condition cannot be fulfilled solely by relying on State Universities. Therefore, the role of private universities is crucial. One of the private universities that can meet this need in the College of Economics. This higher education path is expected to meet the demands for reliable human resources in the economic field, both in the academic world and in the practical world. This condition cannot separate from the role of lecturers in meeting these demands. This study aimed to determine the organizational culture of permanent lecturers in the South Sumatra region. The population in this study were private university lecturers in the South Sumatra region. The research method uses a descriptive survey using descriptive analysis. The number of research samples was 185 respondents/permanent lecturers. The study results illustrate that organizational culture is not good, with two indicators having the lowest value. The indicators in question are doing work carefully and doing work carefully. For this reason, it is necessary to improve indicators by doing work carefully and doing work carefully.